Hidden in plain sight : an archaeology of magic and the cinema / Colin Williamson. - Williamson, Colin
Colin Williamson situates film within a long tradition of magical practices that combine art and science, involve deception and discovery, and evoke two forms of wonder—both awe at the illusion displayed and curiosity about how it was performed. He thus considers how, even as they mystify audiences, cinematic illusions also inspire them to learn more about the technologies and techniques behind moving images. Tracing the overlaps between the worlds of magic and filmmaking, Hidden in Plain Sight examines how professional illusionists and their tricks have been represented onscreen, while also considering stage magicians who have stepped behind the camera, from Georges Méliès to Ricky Jay.